Estrogen, the Peripheral Immune System and Major Depression – A Reproductive Lifespan Perspective - Engler-Chiurazzi, Elizabeth B.; Chastain, Wesley H.; Citron, Kailen K.; Lambert, Lillian E.; Kikkeri, Divya N.; Shrestha, Sharhana S. (Frontiers in Behavioral Neuroscience, 2022)
Major depression is a significant medical issue impacting millions of individuals worldwide. Identifying factors contributing to its manifestation has been a subject of intense investigation for decades and several targets have emerged including sex hormones and the immune system. Indeed, an extensive body of literature has demonstrated that sex hormones play a critical role in modulating brain function and impacting mental health, especially among female organisms. Emerging findings also indicate an inflammatory etiology of major depression, revealing new opportunities to supplement, or even supersede, currently available pharmacological interventions in some patient populations. Given the established sex differences in immunity and the profound impact of fluctuations of sex hormone levels on the immune system within the female, interrogation how the endocrine, nervous, and immune systems converge to impact women’s mental health is warranted. Here, we review the impacts of endogenous estrogens as well as exogenously administered estrogen-containing therapies on affect and immunity and discuss these observations in the context of distinct reproductive milestones across the female lifespan. A theoretical framework and important considerations for additional study in regards to mental health and major depression are provided.